Elderly‐onset degenerative “lumbar spondylotic myelopathy” in a patient with a low‐placed spinal cord successfully treated by laminotomy: a case report - Hashimoto, Ko (Clin Case Rep, 2015)
The authors report a rare case of elderly‐onset “lumbar spondylotic myelopathy” occurred on a low‐placed spinal cord compressed at multiple levels with thickened ligamenta flava. A posterior decompression surgery could alleviate neurological symptoms successfully instead of untethering of the spinal cord, a widely accepted surgery for tethered cord.